The safety of combining immune checkpoint inhibitors and platinum-based chemotherapy for the treatment of solid tumors: A systematic review and network meta-analysis - Mei, Ting; Wang, Ting; Deng, Qianyue; Gong, Youling (Frontiers in Immunology, 2023)
Objective Combination treatment regimens consisting of both immune checkpoint inhibitors (ICI) and chemotherapeutic agents have emerged as the standard of care for a range of cancers. This network meta-analysis (NMA) examined the toxicity profiles and safety rankings of these different ICI-based combination regimens. Methods The PubMed, EMBASE, Web of Science, and Cochrane Library databases were searched for all randomized controlled trials (RCTs) published as of March 1, 2022 comparing two or more treatment regimens in which at least one arm was comprised of an ICI + platinum-based chemotherapeutic regimen. Treatment-related adverse events (AEs) of any grade and AEs of grade 3 or higher were the primary endpoints for this analysis, while specific AE types were secondary endpoints. This NMA combined both direct and indirect comparisons when analyzing odds ratios (ORs) and the surface under the cumulative ranking curve (SUCRA) for different ICI-based treatment regimens. Results In total, 33 RCTs enrolling 19,012 cancer patients were included in this NMA. Of the analyzed regimens, avelumab + chemotherapy and camrelizumab + chemotherapy were associated with a significantly greater risk of AEs of any grade relative to ipilimumab + chemotherapy, durvalumab + chemotherapy, or pembrolizumab + chemotherapy. No significant differences in the risk of AEs of grade 3 or higher were observed when comparing different ICI regimens. Hepatotoxicity and pyrexia were the most common AEs associated with atezolizumab + chemotherapy treatment. Ipilimumab + chemotherapy was associated with a relatively higher risk of gastrointestinal and skin toxicity. Skin toxicity and hypothyroidism were the major AEs associated with nivolumab + chemotherapy. Fatigue and pneumonia were the most common AEs respectively associated with sugemalimab + chemotherapy and pembrolizumab + chemotherapy regimens. Conclusions Of the evaluated regimens, camrelizumab + chemotherapy and avelumab + chemotherapy were associated with significantly higher rates of AEs of any grade, whereas durvalumab and sintilimab were relatively safe PD-L1 and PD-1 inhibitors, respectively, when administered in combination with platinum-based chemotherapy. However, none of the evaluated ICI + chemotherapy regimens exhibited any differences with respect to the incidence of grade 3 or higher AEs, offering guidance that may be of value in routine clinical practice.